The role of the Muslim Brotherhood the post January 25 Egyptian political system - Al Khalifa, Hessa (AUC Knowledge Fountain, 2016)
This thesis analyses the development of the Muslim Brotherhood since their creation until their fall from power in the 30th of June Uprising.